Integrating Al-Ghazali’s Spirituality and Habermas’s Communicative Rationality in the Formation of Holistic Education - Khodijah Amatulloh Sholihat; Benny Prasetya; Muhammad Alfi Syahrin (Immortalis Journal of Interdisciplinary Studies, 2026)
This study aims to conceptually examine the integration of spirituality in Al-Ghazali’s thought and communicative rationality as proposed by Jürgen Habermas as a foundation for developing a holistic educational paradigm. The analysis focuses on how these two perspectives can be understood as bases for human formation through educational processes, as well as on identifying their points of convergence, differences, and potential integration within an educational framework that encompasses both spiritual and dialogical-rational dimensions. This research employs a literature study method by examining the primary works of Al-Ghazali and Habermas, along with relevant scholarly sources addressing education, spirituality, and rationality. The findings indicate that Al-Ghazali’s thought emphasizes spirituality, morality, and character formation as essential value orientations in education, highlighting that educational processes should not merely prioritize cognitive development but also moral and spiritual cultivation. In contrast, Habermas’s theory of communicative rationality underscores the importance of rational, critical, and distortion-free dialogue as a means of fostering reflective and participatory individuals within social life. The integration of these two perspectives offers a holistic educational model that harmonizes spiritual value orientation with dialogical and rational pedagogical practices. Thus, education can contribute to the formation of individuals who are not only morally grounded and spiritually aware but also capable of critical thinking, argumentative communication, and constructive participation in pluralistic and democratic societies.